Zaščita interesov zaposlenih v prevzemnih postopkih po pravu EU in izvedbenem slovenskem pravu - Hojnik, Janja (Delavci in delodajalci, 2014)
The article analyses current regulation of workers' participation at takeover procedures, the possibilities offered as well as its shortcomings. In the first part the article discusses regulation at EU level and in the second part the relevant Slovenian regulation. As the latter is concerned, the author performed an empirical study among works councils' presidents of seven Slovenian companies, which have recently been engaged in takeover procedures, which gives an insight into practical aspects of workers representatives role under takeover procedures. The author concludes that the existing regulation on workers' rights to be informed on takeover does not provide sufficient guarantee to workers in terms of their protection from risk of change of working conditions and redundancies. Instead they are mostly passive observers of procedures and changes, which predominantly aim at meeting the shareholders' interests.
Keywords: direktive; Evropska unija; informacije; informiranje; podjetja; pravice; pravna ureditev; prevzem; Slovenija; zaposleni